Optimizing Pregnancy-related Nausea: Central Composite Design for Fast Relief Buccal Films - Wal, Ankita; Dev, Dhruv; M M, Rekha; Kumawat, Rohit; Singh, Manmeet; Kumar, M Ravi; Wal, Pranay (Current Analytical Chemistry, 2026)
BackgroundNausea and vomiting are common responses to various factors like gastrointestinal disorders, motion sickness, pregnancy, medications, infections, and severe pain. Treatment includes antiemetic medications, hydration, dietary adjustments, rest, and, in severe cases, medical intervention to address underlying causes.ObjectiveThe present research aims at formulating buccal Promethazine with polymers like HPMC E15 and sodium alginate hence relief from the condition of nausea and vomiting in pregnancy.MethodsA variety of PMT buccal films (PBF), comprising varying HPMC E15 and sodium alginate, incorporating PMT (25 mg) in keeping with the method recommended via Design Expert Software, have been fabricated using the solvent casting approach. The design expert software 11.0 trial version was used for statistical analysis of the responses.ResultsThe results showed PMT's compatibility with excipients, preserving the drug's functional groups. The films were neutral, and flexible, with uniform thickness and good swelling, especially in sodium alginate-rich films. They had consistent drug content, and mucoadhesion time and strength increased with HPMC E15 concentration. In vitro tests revealed a 40% burst release in 10 minutes, followed by varied release rates based on polymer composition.ConclusionThe optimized buccal films showed greater flexibility and a promising balance between swelling, which is necessary for drug release, and mucoadhesion, which prolongs mucosal contact. The buccal films' optimized features suggest that controlled and prolonged release could improve Promethazine absorption and therapeutic efficacy. The ease of administration and longer mucosal retention period may improve patient compliance and experience.
Keywords: Antiemetic